Pain Processing in Psychiatric Conditions: A Systematic Review. Issue 3 (September 2019) - Vaughan, Sarah; Failla, Michelle D.; Poole, Helen M.; Forshaw, Mark J.; McGlone, Francis; Cascio, Carissa J.; Moore, David J.
Pain is a universal, multidimensional experience with sensory, emotional, cognitive, and social components, which is fundamental to our environmental learning when functioning typically. Understanding pain processing in psychiatric conditions could provide unique insight into the underlying pathophysiology or psychiatric disease, especially given the psychobiological overlap with pain processing pathways. Studying pain in psychiatric conditions is likely to provide important insights, yet, there is a limited understanding beyond the work in depression and anxiety. This is a missed opportunity to describe psychiatric conditions in terms of neurobiological alterations. To examine the research into the pain experiences of these groups and the extent to which a-typicality is present, a systematic review was conducted. An electronic search strategy was developed and conducted in several databases. The current systematic review included 46 studies covering five Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5 ) disorders: autism, attention-deficit hyperactivity disorder (ADHD), schizophrenia, personality disorder, and eating disorders, confirming tentative evidence of altered pain and touch processing. Specifically, hyposensitivity is reported in schizophrenia, personality disorder and eating disorder, hypersensitivity in ADHD, and mixed results for autism. Review of the research highlights a degree of methodological inconsistency in the utilization of comprehensive protocols, the lack of which fails to allow us to understand whether a-typicality is systemic or modality specific.